Beyond extractivism and alternative cosmologies:arctic communities and extractive industries in uncertain times - Wilson, Emma; Stammler, Florian (The Extractive Industries and Society, 2016)
The Arctic remains of great interest for extractive industry development, despite fluctuating mineral and hydrocarbon prices, and the technological and political challenges of accessing these resources. The articles in this special section explore the realities of living close to extractive industries in the Arctic; the expectations surrounding extractive projects; the nature of local and distributed benefits; and the extent to which local knowledge is incorporated into public debates. In this introduction, we consider how an ‘extractivist’ logic can stifle other ways for local communities to imagine the future, contrasting this with local perspectives based on sustainability and co-existence with nature. Where industrial activity takes place, local involvement in shaping an industry’s ‘social licence to operate’ offers a counterbalance to an ‘extractivist’ imperative, by focusing more on equitable benefit sharing and protection of local livelihoods and the environment. We conclude that rights holders and others directly affected by industry operations can use their own knowledge to ensure that decisions are sensitive to longer-term sustainability risks, and that alternative development options are adequately considered. An empowered local civil society also has an important role in ensuring extractive industry operations are environmentally sound and compatible with existing local livelihoods.